Bioproduction of Linalool From Paper Mill Waste - Rinaldi, Mauro A.; Tait, Shirley; Toogood, Helen S.; Scrutton, Nigel S. (Frontiers in Bioengineering and Biotechnology, 2022)
A key challenge in chemicals biomanufacturing is the maintenance of stable, highly productive microbial strains to enable cost-effective fermentation at scale. A “cookie-cutter” approach to microbial engineering is often used to optimize host stability and productivity. This can involve identifying potential limitations in strain characteristics followed by attempts to systematically optimize production strains by targeted engineering. Such targeted approaches however do not always lead to the desired traits. Here, we demonstrate both ‘hit and miss’ outcomes of targeted approaches in attempts to generate a stable Escherichia coli strain for the bioproduction of the monoterpenoid linalool, a fragrance molecule of industrial interest. First, we stabilized linalool production strains by eliminating repetitive sequences responsible for excision of pathway components in plasmid constructs that encode the pathway for linalool production. These optimized pathway constructs were then integrated within the genome of E. coli in three parts to eliminate a need for antibiotics to maintain linalool production. Additional strategies were also employed including: reduction in cytotoxicity of linalool by adaptive laboratory evolution and modification or homologous gene replacement of key bottleneck enzymes GPPS/LinS. Our study highlights that a major factor influencing linalool titres in E. coli is the stability of the genetic construct against excision or similar recombination events. Other factors, such as decreasing linalool cytotoxicity and changing pathway genes, did not lead to improvements in the stability or titres obtained. With the objective of reducing fermentation costs at scale, the use of minimal base medium containing paper mill wastewater secondary paper fiber as sole carbon source was also investigated. This involved simultaneous saccharification and fermentation using either supplemental cellulase blends or by co-expressing secretable cellulases in E. coli containing the stabilized linalool production pathway. Combined, this study has demonstrated a stable method for linalool production using an abundant and low-cost feedstock and improved production strains, providing an important proof-of-concept for chemicals production from paper mill waste streams. For scaled production, optimization will be required, using more holistic approaches that involve further rounds of microbial engineering and fermentation process development.